Communicable Diseases Intelligence volume 13 issue 11 - 5 June 1989 - whole issue - No author listed (Communicable Diseases Intelligence, 1989)
Whole-issue pdf, comprising: Viruses, Chlamydias, Coxiellas, Rickettsias and Mycoplasmas Reporting Scheme Original article Gonococcal surveillance, Australia: 1 October - 31 December 1988. U.S. Immunization Practices Advisory Committee (ACIP): general recommendations on immunisation Australia - Communicable Diseases Intelligence Period 11/05/1989 to 24/05/1989